A Method for Deconvoluting and Quantifying the Real‐Time Species Fluxes and Ionic Currents Using In Situ Electrochemical Quartz Crystal Microbalance (Adv. Mater. Interfaces 16/2022). Issue 16 (3rd June 2022) - Zheng, Kai; Xian, Yongqiu; Lin, Zifeng
Abstract : Deconvoluting and Quantifying Real‐Time Species Fluxes and Ionic Currents In article number 2200112, Kai Zheng, Yongqiu Xian, and Zifeng Lin provide a method for deconvoluting and quantifying the real‐time species population, fluxes, and corresponding ionic currents from conventional in situ electrochemical quartz crystal microbalance measurements. Flux cyclic voltammograms (CV) and ionic current CV are proposed for better interpreting the potential‐dependent specie flux and ionic current evolution. As a proof of concept, Ti3 C2 T x MXene capacitive electrode in 1 m H2 SO4 electrolyte is investigated.